The Importance of Vitamins and Microelements in Cattle Organisms - Komiljonov Sukhrobbek Komоladdinovich (Scientific Trends, 2025)
This article presents the results of experimental trials on 15 large horned animals (3, 12, and 18 months old) at the Qo‘niratbay mexri farm in Nukus district of Karakalpakstan Republic. The trials evaluated the effectiveness of Antimyopatic-2 and E-selenium preparations. An average weight gain of 683.3 grams per animal was observed when 2 ml of Antimyopatic-2 was administered per animal, while an average weight gain of 500 grams per animal was observed when 2 ml of E-selenium was administered. Animals fed the same diet without any administered medication showed an average weight gain of 150 grams.
Keywords: Vitamin, biochemical reactions, rickets, Antimyopathic-2, E-selenium, Microelement, iron (Fe), zinc (Zn), iodine (I), selenium (Se), fluorine (F), copper (Cu), manganese (Mn), cobalt (Co), minerals.